Consumer Perceptions of Sustainability Labels on Fashion Products and Their Influence on Purchase Intention - Priyanto, Agung Wicaksono; Putri, Rizky Amalia; Qosidah, Nanik (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The fashion industry ranks amongst the sectors with the most environmental impacts. Hence, companies are adopting sustainable practices, such as sustainability labeling. Yet, bridging the positive attitudes of consumers with their actual purchasing behavior (the attitude-behavior gap) is a major hurdle facing this industry, especially in Indonesia. This study investigates consumers' perceptions toward sustainability labels in terms of clarity, credibility, and trust, as well as their effects on consumers' intentions to purchase sustainable products in fashion. This research followed a mixed-method approach constructed in a sequential explanatory design. Quantitative data were collected from 350 respondents via an online survey, and analyzed using SEM-PLS, while qualitative data were obtained through semi-structured interviews with 15 participants, followed by thematic analysis. Results show that all dimensions of perception are significant determinants of purchase intention (R² = 0.58). As a dominant factor, label clarity has a greater impact than both credibility and trust. Qualitative results confirm that clear and interpretable labeling raises consumer confidence toward the purchase of sustainable products, even if the issue of greenwashing creates doubt. The contribution of this study is to conceptualize and demonstrate, within a developing-country context that remains underexplored, that sustainability labels indeed shape consumer attitudes and directly influence actual purchasing. The industry should focus on designing simple, credible, and verifiable labels, while policymakers would also benefit from these insights as a foundation to formulate national labeling standards in order to increase public trust in and promote sustainable consumption.